ANTI-CANCER AND OXIDANT PROPERTIES OF DIFFERENT SESQUITERPENE LACTONES ISOLATED FROM INDIGENOUS LEBANESE PLANTS - Ghantous, A.; Gali-Muhtasib, H.; Saliba, N.; Darwiche, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Most cancers are of epithelial origin of which skin cancer is the most frequent. Numerous naturally occurring compounds have been identified as skin chemopreventive agents, and many of the best-selling anticancer drugs are plant-derived. While screening for anti-cancer activities of forty-four Middle Eastern plant extracts used in folk medicine, we identified the Lebanese indigenous plants, Centaurea ainetensis and Achillea falcata, to possess potent and selective activities against cancer cells. Bioassay-guided fractionation of these plants’ crude extracts led to the isolation of the sesquiterpene lactone family of plant secondary metabolites having the most potent anti-tumor activities. These included two guaianolides from C. ainetensis: Salograviolide A (Sal-A) and its hydroxy-isomer and four seco-guanolide derivatives from A. falcata: Tanaphillin, 3-beta-methoxy-3-deshydroxy-iso-seco-tanapartholide (beta-Tan), iso-seco-tanapartholide, and 8-hydroxy-3-methoxy-iso-seco-tanaparatholide. We determined the growth inhibitory effects of the isolated sesquiterpene lactones on the human epidermal HaCaT cells, a well characterized model for early stage skin carcinogenesis, and correlated these activities with oxidant potential. We found that Sal-A and beta-Tan exhibited the most potent growth inhibitory effects at concentrations that were not cytotoxic to primary human keratinocytes. Sal-A caused pre-G0/G1 cell cycle arrest and reduced cyclin D1 proteins while beta-Tan induced G2/M arrest and decreased cyclin B1 proteins. Sal-A- and beta-Tan-induced growth inhibition was preceded by an early and progressive accumulation of reactive oxygen species (ROS). Pre-treatment with different anti-oxidants reduced drug-induced ROS generation and abrogated growth inhibition. These studies provide a rationale for designing plant-derived anti-cancer drugs from sesquiterpene lactones.